An educational study on gadget addiction and mental health among Gen Z - Surat, Shahlan; Govindaraj, Yamuna Devi; Ramli, Shalinawati; Mohamad Yusop, Yusni (Scientific Research Publishing, 2021)
The acceleration of modern technology in the techno gadget era has led to the transformation of modern media highlighted by Generation Z. The aim of this study is to explore how gadget addiction influences the level of depression, anxiety, stress and sleep quality among the samples from the Ministry of Health Training Institution Sungai Buloh, Malaysia. Using the stratified sampling method, a total of 316 college students from various field are surveyed on the Smartphone Problematic Use Questionnaire, Depression Anxiety Stress Scale and Pittsburg Sleeping Quality Index. The Pearson correlation analysis and linear regression are adopted to find the relationship among the variables. Results show that gadget addiction is a predictor of depression, anxiety, stress and sleep disturbances. The findings of descriptive analysis show that the level of addiction, depression, anxiety and stress among the trainers is high. Positive correlations are found between the gadget addiction and levels of depression, anxiety, stress and sleep quality. Levels of depression, anxiety, stress and sleep quality among trainers are significant, with 13%, 10.7%, 12.5% and 3.4% experiencing symptoms of depression, anxiety, stress and sleeping disturbance respectively. Therefore, it is generally possible to know that the problem of gadget addiction can interfere with mental health of the users if the use of gadgets is not well controlled. The implications of this study are useful to academics and heavy gadget users and those who are hooked with their gadgets in their everyday life. Further studies in this area are needed to delve deeper into other issues related to each element of gadget addiction in order to reinforce the research framework which will in turn develop a standard guide for controlling gadget use in Malaysia.